AN UNREASONABLE PURCHASE OF GOODS: A CRIMINAL LAW PERSPECTIVE - Kuswardani; Kurnianingsih, Marisa; Hussain, Mazlena Mohamad; Prokosa, Andria Luhur; Fairuzzaman, Fahmi (Awang Long Law Review, 2025)
The purpose of this study is to compare the criminal law regarding the dishonest purchase of goods or receipt of goods resulting or also known as fencing from crime between the Indonesian Criminal Code and the Penal Code of Singapore. This research uses a normative juridical method, so the data used is secondary. This data consists of the Indonesian Criminal Code and the Singapore Penal Code, as well as journals relevant to the problem. The novelty of this research is that the formulation of criminal sanctions is not only alternative but can be imposed cumulatively, and there is a separate formulation regarding the receipt of stolen motor vehicle goods. The research results show that purchasing criminal goods or receiving stolen property or fencing is regulated under Article 480 of the Indonesian Criminal Code and Article 411 of the Singapore Criminal Code. Both define the offense as intentional by a responsible perpetrator. Criminal sanctions under the Indonesian Criminal Code are alternative, and if fencing occurs, there is jurisprudence as source of formal law. While those under the Singapore Penal Code are alternative or cumulative. Receiving stolen property, particularly motor vehicles, carries cumulative penalties, plus a ban on holding or obtaining a driver's license, imposed by the court upon release from prison. The research concludes that fencing is a violation in both Indonesia and Singapore. The only differences lie in the form of punishment stipulated in the Criminal Code and the formulation of receiving stolen property for motor vehicles. The research concludes that fencing is a violation in both Indonesia and Singapore. The only differences lie in the form of punishment stipulated in the Criminal Code and the formulation of receiving stolen property for motor vehicles.